UMP researchers bag 5 awards at British Invention Show 2009 - UMP, PNC
Two researchers from University Malaysia Pahang (UMP) did the university proud when they collectively bagged three gold medals and two special awards at an international level innovative competition – the British Invention Show (BIS 2009) – in London, United Kingdom, last year.